Contribution of the chair phthisiological to TB control - Cano Gironda, L. (1956)
We must show that the contribution of the Department of Tisiología to TB control that performs the appropriate Division of the Ministry of Public Health and Social Assistance, started last 18 years has been characterized by an ongoing technical assistance and has covered aspects doctrine in the planning and development of control programs; in the selection of medical personnel assigned to fill technical positions Tuberculosis Campaign, with the participation of Professor of the Department, as an integral member of the jury of the evidence for the respective competitions; and finally by the Supreme Order of F ~ July 1955, has formalized the close cooperation regarding tuberculosis were carrying out those engineering personnel (Faculty of Medicine, Department of Tisiología) and those who use in control programs TB (tuberculosis Division of the Ministry of Public Health) signifying the continued development of courses for training in the specialty of graduates; more specialized training and familiarization of the general practitioner in the precocious, individual and collective diagnosis of tuberculosis in the rational treatment with new therapeutic resources and know when a TB case should be transferred to the thoracic surgeon's hands.